Simulation of two phase oil-gas flow in pipeline - Pao, W. (Asian Research Publishing Network, 2016)
T-junction, or commonly known as stand pipe appendage, is used by oil/gas industries to tap gas from existing production header for the purpose of downstream pipeline instrumentation. The appendage is either pre-design or retrofitted with minimum internals for maximum reliability for remote deployment. The motivation for this research originated from the lack of stand-pipe design method to correctly account for the splitting/separation nature of multiphase fluid within the pipeline straight from the production header. Consequently, a certain amount of liquid migrates together with the gas, resulting in the so-called carryover issue. This situation is further aggravated by the different flow regimes in the header pipeline which is not taken into account by the design practice. The negative consequences of this carryover on the operation of downstream unit have often led to frequent trip and maintenance issues. This paper presents the preliminary research in the finding of the two phase oil/gas separation in T-junction. The computed solutions are compared with experimental data and a good agreement is achieved. Â© 2006-2016 Asian Research Publishing Network (ARPN).